Peran Kepala Madrasah Sebagai Manajer Dalam Peningkatan Kinerja Tenaga Administrasi Di MA Miftahul Ulum Cermenan Ngoro Jombang - Binti Masrufa; Zuhra Harun (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2023)
The principal as a manager has a very decisive role success in an institution he leads, the success or failure of madrasa goals can be influenced by how the madrasa head performs management functions. In order to carry out its roles and functions as a manager. This study aims to describe 1. The role of the madrasa head as a manager in improving the performance of administrative staff at MA Miftahul Ulum Cermenan Ngoro Jombang 2. The performance of administrative staff in the field of student affairs at MA Miftahul Ulum Cermenan Ngoro Jombang. This research is a qualitative field research, the research design is descriptive qualitative using data collection techniques, namely observation, interviews, and documentation. Furthermore, data analysis was carried out using qualitative methods with a qualitative descriptive design. The results showed that: 1. The role of the head of the madrasa as a manager at MA Miftahul Ulum Cermenan Ngoro Jombang, namely: a. compiling the program: The head of the madrasa forms a special committee, b. madrasa organization: the head of the madrasa forms a work team contained in the hierarchical organizational structure. c. mobilize staff: the head of the madrasa directly supervises his employees in completing madrasa tasks. 2. Performance of administrative staff at MA Miftahul Ulum Cermenan Ngoro Jombang. It can be seen from: a. Quantity of work achieved: the work of administrative staff is always monitored by the head of the madrasa, so that all tasks are completed according to procedure, b. quality of work achieved: accuracy in work, work discipline, adherence to work procedures c. the quality of the work the ability to do the job as required d. attendance and activities while present at the workplace.